Odpowiedzi

2010-03-08T16:48:21+01:00
Y - 6x = 0
4x - y = -2

y = -6x
4x - y = -2

y = -6x
4x - (-6x) = -2

y= -6x
10x = -2

y= -6x
x = -0.2

y= -1.2
x= -0.2

(4^14*4^2) : (4^8*4^5) =
4^16 : 4^13 =
4^3 = 64
2010-03-08T16:51:16+01:00
1.
y - 6x = 0
4x - y = -2

skracamy "y" z "-y"
-6x + 4x = 0 + (-2)

-2x = -2
x = 1

2.
( 4 do potęgi 14 * 4 do potęgi 2 ) : ( 4 do potęgi 8 * 4 do potęgi5)
(4 do potęgi 14 + 2) : (4 do potęgi 8 + 5)
4 do potęgi 16 : 4 do potęgi 13
4 do potęgi 16 - 13
4 do potęgi 3 = 64
2010-03-08T17:23:58+01:00
Y-6x=0
4x-y=-2

y=0+6x
4x-(0+6x)=-2

y=0+6x
4x-0-6x=-2

y=0=6x
-2x=-2 /:(-2)

y=0+6x
x=1

y=6
x=1

(4^14 * 4^2) : (4^8 * 4^5)= (268435456 * 16) : (65536 * 1024)= 4294967296 : 67108864= 64